Assessment of hospital-based adult triage at emergency receiving areas in hospitals in Northern Uganda - Opiro, Keneth (Division of Emergency Medicine, 2017)
Background: Limited health service resources must be used in a manner which does "the most for the most". This is partly achieved through the use of a triage system, but health workers must understand it, and it must be used routinely. Whereas efforts have been made to introduce paediatric triage in Uganda, such as Emergency Triage Assessment and Treatment Plus (ETAT+), there is no unified adult triage system being used in Uganda, and it is not clear if hospitals have local protocols being used in each setting. There are limited data on adult triage systems in Uganda. This study aimed at determining how adult hospital-based triage is performed in hospitals in northern Uganda. Methodology: This was a descriptive study. Allocating numbers to the three sub-regions in the northern region, and using a random number generator, we randomly selected the Acholi sub-region for the study. The study was conducted in 6 of the 7 hospitals in the region - one hospital declined to grant permission for the research. It was a written questionnaire survey under supervision of the investigator. In each hospital, at least one representative of nurses in various duty shifts (night, morning and evening shifts), the nursing in-charge/leader, at least one doctor (head of department or any doctor on duty, if available) and a clinical officer (physician assistant, if available), making a minimum of 5-6 study participants who were health professional staff working in emergency receiving areas from each hospital consented and participated in the study. Results: Thirty-three participants from 6 hospitals including 5 doctors, 4 physician assistants, 11 registered nurses, 9 enrolled nurses and 4 nursing assistants consented and participated in the study. Experience of staff working in emergency receiving areas varied with 15(45.5%) greater than 2 years, 7(21.2%) 1-2 years, 5(15.2%) 6 - <12 months and 6(18.2%) for less than 6 months. Only one hospital (16.7%) of the 6 hospitals surveyed had a formal adult hospital-based triage protocol in place. The triage guide/protocol/charts were kept in drawers, had 3 colours - red, yellow and green. Staff rated it as "good", and all staff acknowledged the need to improve it. Only 2 (33.3%) hospitals had an allocated emergency department, the rest receive emergency patients/perform triage from Out Patient Department (OPD) and wards. Lack of training, variation of triage protocols from hospital to another, shortage of staff on duty, absence of national guidelines on triage and poor administrative support were the major barriers to improving/developing formal triage in all these hospitals. Conclusion: Formal adult, hospital-based triage is widely lacking in northern Uganda, and staff do perform subjective "eyeball" judgments to make triage decisions. Most hospitals do not have specifically allocated emergency department which risks disorganization in the flow of patients, crowding and consequently worse patient outcomes.